Using lean six sigma to achieve competitive advantage Applied research in the General Company for Electrical Industries/Waziriya "Engine Lab" - محمد عبد الواحد فليح; أشواق طالب كاظم (Journal of Madenat Alelem University College, 2019)
The development of products is one of the challenges faced by economic units. As competition grows, the introduction of new products and the ability to develop them and increase their quality continuously is a major reason for success. has developed the problem of research at high costs now Through the increase in the number of damaged units and bearing the unit with all elements of production of direct materials and direct wages and indirect industrial costs, which leads to bear the costs of damaged units on the production of sound, which increases production costs while the research aims to demonstrate the concept of elegance and six-party movement encountered similarities and differences between them and clarify the concept of diffraction And the application of the graceful six-party diffraction in the General Company for Electrical Industries and how to achieve competitive advantage while the research has reached the use of graceful vertical diffraction represents a cultural change at all levels of unity Economic, with emphasis on senior management level, as should the time commitment, energy and resources to promote the lea Six-sigma.